Sustainable historic urban landscapes using a morphological approach at different scales - Ardicoglu, Ruya (Nova Science Publishers Inc., 2025)
In recent decades, historical conservation and development approaches have been developed within the scope of landscape-based applications. Despite recent developments, owing to the uniqueness of historic sites and the dynamic nature of urban systems, methodologies, approaches, and tools of historic urban landscapes (HUL) should be diverse and comprehensive for different urban scenarios. This chapter focuses on the physical elements that embodied the urban landscape and aims to handle the HUL in a morphological view at different scales. The main goal is to develop a hierarchical approach to the physical elements of urban landscapes. Associating HUL with a morphological approach and developing a hierarchical view of physical elements can be used in the management strategies of historic urban landscapes. Physical components are classified into three scales to ensure the sustainability of historic urban landscapes: macro, meso, and micro. Firstly, at the macro scale, the town plan and its role in the sustainability of urban landscapes and the control of urban development are handled. Second, at the meso scale, architectural typology, building alignment, and streetscape are explained. In the third step, at the micro scale, materials, texture, color, and vegetation are defined as the detailed criteria for the conservation and development of the HUL. The chapter addresses the influence of urban metamorphosis on physical elements at different scales. It explains how these components influence each other and the sustainability of historic landscapes. It also focuses on how they should be managed in dynamic urban flow. Understanding the horizontal relations of urban elements at the same scale, as well as their vertical relations from the macro to micro scale, can help to solve management problems within the dilemma of conservation and development. © 2025 by Nova Science Publishers, Inc.
Keywords: Historic urban landscape; Management of change; Sustainability; Urban landscape; Urban morphology